Book Review: Airport Competition: The European Experience - Pratama, Garry Gumelar (Faculty of Law, Padjadjaran University, 2017)
The competitive business environment in aviation industry has changed since European Integration. Not only airlines become more competitive after sÂuch integration, but also other main infrastructure of aviation, airports. At the first stage of regional development, competition in airport industry seems to be impossible since all countries in a region still have clear jurisdictional boundaries. The other side of the coin is that airport competition becomes an important issue in a more integrated region, such as European Union (EU). This occurs because an airport owner from another country can buy other airports outside its state jurisdiction, under the same region. Articles in this book prove the claim of the existence of airport competition. Under the introductory part, the editors outlined three cases from EU: UK Civil Aviation Authority action to Heathrow Airport in 2008, Blocked Takeover of Bratislava Airport 2006 and European Commission Prohibition on Subsidies to Ryanair by Brussels South Charleroi Airport 2004. All of the cases are inevitable proofs that airport competition undoubtedly exists in Europe.Â Â DOI: https://doi.org/10.22304/pjih.v4n1.a11